Modelling Housing Demand Factors for Affordable Units in Malaysia - Ab Majid, Rohayu; Said, Rosli; Ab Rahim, Norbaya; Ahmad Saleh, Ahmad Fawwaz; Suryanto, Tulus (International Journal of Sustainable Construction Engineering and Technology, 2023)
The Malaysian government is prioritizing the development of affordable housing units to cater to the needs of the underprivileged. However, it is not sufficient to merely meet the required number of units; it is crucial for developers to understand the actual demand for affordable housing in urban areas. This is because even middle-class homebuyers have their own preferences when it comes to purchasing a home at an affordable price. Therefore, this study aims to investigate the current demand attributes that contribute to the affordable housing demand model in urban areas, using Wangsa Maju, Kuala Lumpur, Malaysia as a case study. Data was collected from 400 potential buyers of affordable housing units, and 25 significant attributes of housing demand were examined. Partial Least Square Equation Modelling (PLS-SEM) was used to develop the housing demand model. The findings revealed that a total of five factors with nine attributes in housing demand significantly contribute to the affordable housing demand model in urban areas, as determined by the coefficient’s determination, path coefficient, effect size, and predictive relevance towards endogenous variables of housing demand. Overall, the result has confirmed that government intervention has play major role in supporting affordable housing development and at the same time has encourage the potential buyer form the right group to have their own house at affordable price.